PENGARUH MEDIA SOSIAL FACEBOOK DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASION DI EPIFANY COLLECTION PADA MASYARAKAT MANGGARAI - Yohana Maria Dolorosa Mahin; Dignasaritika Nahung; Yosefina E. Suhartini (Jurnal Ekonomi Dan Bisnis, 2026)
The purpose of this study was to determine the effect of Facebook social media and customer satisfaction on purchasing decisions for fashion products at Epifany Collection in the Manggarai community. The type of this research is quantitative. The sample determination using purposive sampling method that consist of 50 respondents. Data collection techniques using online questionnaires through google forms. Data analysis using the SPSS version 29 program facility with validity test, reliability test, classical assumption test, and hypothesis testing